2017
DOI: 10.3390/app7030277
|View full text |Cite
|
Sign up to set email alerts
|

A Truly Second-Order and Unconditionally Stable Thermal Lattice Boltzmann Method

Abstract: An unconditionally stable thermal lattice Boltzmann method (USTLBM) is proposed in this paper for simulating incompressible thermal flows. In USTLBM, solutions to the macroscopic governing equations that are recovered from lattice Boltzmann equation (LBE) through Chapman-Enskog (C-E) expansion analysis are resolved in a predictor-corrector scheme and reconstructed within lattice Boltzmann framework. The development of USTLBM is inspired by the recently proposed simplified thermal lattice Boltzmann method (STLB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Also, a uniform grid with 128 × 128 meshes was used in all simulations. Comparison of isotherms between present study results and that of Chen et al (2017) is shown in Figures 11 to 14.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Also, a uniform grid with 128 × 128 meshes was used in all simulations. Comparison of isotherms between present study results and that of Chen et al (2017) is shown in Figures 11 to 14.…”
Section: Resultsmentioning
confidence: 65%
“…Comparison of isotherms between the present study (dashed lines) and the study of Chen et al (2017) (solid lines) for Ra = 50,000 (left figure), velocity vectors in the present study (right figure)…”
Section: Figurementioning
confidence: 62%
See 1 more Smart Citation
“…This feature ensures efficiency in computing and simplicity in programming and has led the LBM to be a popular method in recent decades (Guo et al 2002;Mehravaran and Hannani 2008;Huang et al 2009b;Lee and Liu 2010;Zhou et al 2012;Galindo-Torres et al 2013;Lin et al 2013;Galindo-Torres 2013;Galindo-Torres et al 2016;de Rosis 2017;Yang et al 2018Yang et al , 2019Chen et al 2020;Verdier et al 2020;Ru et al 2021;Wang et al 2021;Zhang et al 2021). Chen et al developed an improved version of the simplified LBM (SLBM) (Chen et al 2017(Chen et al , 2018Chen and Shu 2020a, b).…”
Section: Article Highlightsmentioning
confidence: 99%
“…Recently, Chen et al [24][25][26][27] proposed a simplified thermal LBM (STLBM), [24][25][26][27] which only involves macroscopic variables. Therefore, STLBM needs less memory size, and the boundary conditions are easy to implement.…”
Section: Introductionmentioning
confidence: 99%